Inducing oxide ion vacancies in Sr2CoSbO6 as a strategy to decouple power factor and thermal conductivity. (15th September 2022) - Ramesh, Manickam; Biswas, Krishnendu
Abstract : Ti doping in Sr2 CoSbO6 resulted in 16 times increase in power factor and reduction of thermal conductivity by half the original value attributed to the induced oxide ion vacancies. Abstract : In this correspondence, we demonstrate the effect of substituting a d 0 metal ion like Ti 4+ in the place of a d 10 metal ion like Sb 5+ in Sr2 CoSbO6 double perovskite on its thermoelectric properties. Ti substitution led to an enormous decrease in resistivity from a value of 15.59 Ω cm to 0.17 Ω cm, which resulted in an increment of 16 times in the power factor. Also the doping resulted in considerably lowering the thermal conductivity by half the value of the parent compound. The reason is attributed to the induction of oxide ion vacancies in the crystal structure, which acted both as an electron sink and a phonon scatterer. Such a trend in a material is essential for exhibiting a high dimensionless figure of merit value and can be applied in related oxide compounds tolerating oxide ion vacancies.